Oral hygiene habits, denture cleanliness, presence of yeasts and stomatitis in elderly people - (:unkn) unknown (BLACKWELL PUBLISHING LTD, 2002)
The purpose of this study was to determine oral hygiene habits, denture cleanliness, presence of yeasts and denture stomatitis in elderly people. Seventy complete denture wearers were investigated clinically and mycologically. Subjects were evaluated according to, presence of denture stomatitis, presence of yeasts, denture cleanliness, frequency of denture brushing and denture cleaning methods. Swabs were taken from the palate investigated mycologically in order to identify the yeast colonies. No statistical relationship was found between denture stomatitis and frequency of denture brushing and denture cleaning methods. However, there was a statistically significant relationship between denture stomatitis, yeasts' presence and denture cleanliness.
Keywords: denture stomatitis; oral hygiene; elderly people; PLAQUE; MUCOSA